2002
DOI: 10.1238/physica.regular.065a00046
|View full text |Cite
|
Sign up to set email alerts
|

Revised and Extended Analysis of the Ag II Spectrum and Term System

Abstract: The Ag II spectrum emitted from hollow cathode discharges has been recorded in the region 940^8500 Ð with Fourier transform and high dispersion photographic instruments. 311 lines have been classi¢ed and measured at high accuracy (AE0.03^0.003 cm À1 above 2000 Ð, AE0.002^0.0005 Ð in the VUV region). Improved energy level values have been derived from the lines, and 24 new odd levels have been found. The level structure has been interpreted by ab initio and parametric calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 20 publications
(45 reference statements)
1
43
0
Order By: Relevance
“…The calculated eigenvalues of the Hamiltonian were optimized to the observed energy levels via a least‐squares fitting procedure using the available experimental energy levels. In fact, all the levels taken from the NBS compilation (NIST 2005b), including refined values due to Benschop et al (1975) and to Kalus et al (2002), were included in the fitting procedure. The scaling factors of the F k , G k and R k integrals (not optimized in the least‐squares fitting procedure) were chosen equal to 0.80, while the spin–orbit integrals were left at their ab initio values.…”
Section: Hfr Calculationsmentioning
confidence: 99%
“…The calculated eigenvalues of the Hamiltonian were optimized to the observed energy levels via a least‐squares fitting procedure using the available experimental energy levels. In fact, all the levels taken from the NBS compilation (NIST 2005b), including refined values due to Benschop et al (1975) and to Kalus et al (2002), were included in the fitting procedure. The scaling factors of the F k , G k and R k integrals (not optimized in the least‐squares fitting procedure) were chosen equal to 0.80, while the spin–orbit integrals were left at their ab initio values.…”
Section: Hfr Calculationsmentioning
confidence: 99%
“…The most complete previous analysis of the Ag II spectrum was made by Kalus et al [ 1 ]. These authors measured the spectrum emitted by a pulsed hollow-cathode discharge in the region 940 Å to 8500 Å.…”
Section: Introductionmentioning
confidence: 99%
“…Kalus et al [ 1 ] noted that their line list does not include many of the lines reported by earlier observers. In particular, they mentioned that Gilbert [ 2 ] was able to observe many more combinations between highly excited levels by using a condensed hollow-cathode discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The atomic energy level structure of Nb ii was extended by Ryabtsev et al (2000) as part of a project at Lund which aim at improving the atomic data for the singly ionized 4d-transition group. Within this project the term analyses of Y ii (Nilsson et al 1991), Mo ii (Nilsson & Pickering 2003), Ru ii (Karlsson et al 2002), Pd ii (Litzén et al 2001) and Ag ii (Kalus et al 2002) have been published, and analyses of Zr ii and Rh ii are in progress. Oscillator strengths have been measured in Zr ii (Sikström et al 1999;Ljung et al 2006), Mo ii (Sikström et al 2001), Ru ii (Johansson et al 1994) and Pd ii (Lundberg et al 1996).…”
Section: Introductionmentioning
confidence: 99%